Influence of vertical greenery systems and green roofs on the indoor operative temperature of air-conditioned rooms. (September 2020) - Hao, Xiaoli; Xing, Qingwei; Long, Pinhan; Lin, Yaolin; Hu, Jinhua; Tan, Hang
Abstract: Over the last decade, the influences of vertical greenery systems (VGSs) and green roofs (GRs) on indoor air temperature, surface temperature of walls, and energy consumption have been widely investigated. There is little information on how VGSs and GRs influence the indoor operative temperature of an air-conditioned space, even though it is a measure of human thermal comfort. This study experimentally investigates the effects of VGS and GR on indoor operative temperatures. Two experimental rooms, one equipped with VGS and GR and the other without, are constructed in Xiangtan, China, which is located in the hot summer and cold winter climate zone. The rooms are controlled using identical indoor air temperature set-points. During the experiments in summer 2018, the indoor and outdoor thermal environmental parameters were measured and recorded automatically. The results indicate that the operative temperature of the room with VGS and GR was reduced by 0.4 °C on average and a maximum of 2.1 °C compared to the room without VGS and GR. The impact of VGS and GR on the operative temperature in the daytime is greater than at night. In addition, the VGS and GR also decrease the oscillation of the operative temperature, and a more stable thermal environment can be achieved with VGS and GR. A computer program was developed using EnergyPlus, and the results were validated using experimental data. By performing computer simulations during the whole cooling season (from June 1 to September 30), it was found that the operative temperature of the room with VGS and GR was reduced by 0.59–0.65 °C during the daytime (7:00 a.m.–7:00 p.m.) and remained almost unchanged at night. Further, the set-point temperature of the room with VGS and GR can be 0.76–0.84 °C higher than that of the room without VGS and GR in the daytime to maintain the same level of thermal comfort. An energy saving correction from 7% to 8% on the daytime energy consumption is proposed with this increased set-point temperature. Highlights: Influence of vertical and roof greenery system on air-conditioned space was studied. Average reduction of 0.6 °C on daily indoor operative temperature was found. The oscillation of indoor operative temperature was depressed by 1.1 °C. An energy saving correction of 7–8% was proposed in the analysis of saving potential.